2022
DOI: 10.3390/toxics10020068
|View full text |Cite
|
Sign up to set email alerts
|

Differential Uptake and Translocation of Cadmium and Lead by Quinoa: A Multivariate Comparison of Physiological and Oxidative Stress Responses

Abstract: Contamination of soils with cadmium (Cd) and lead (Pb) has emerged as a serious environmental issue that reduces crop productivity. However, the metals tolerance and accumulation potential of quinoa (Chenopodium Quinoa Willd) under the combined stress of Cd and Pb has not yet been explored. In the present hydroponic study, the physiological and biochemical characteristics of quinoa exposed to Cd and Pb were explored. Four-week-old plants of quinoa genotype ‘Puno’ were grown under different concentrations of Cd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 41 publications
(115 reference statements)
1
12
0
Order By: Relevance
“…It was observed that both the salinity and Cd decreased plant growth attributes; however, their combined stress was more detrimental for the plant growth of quinoa. A decline in the growth of quinoa and other plants under Cd stress is well reported [6,20,21]. Cadmium, after being taken up by plant roots, is accumulated in different parts of the plants [22].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…It was observed that both the salinity and Cd decreased plant growth attributes; however, their combined stress was more detrimental for the plant growth of quinoa. A decline in the growth of quinoa and other plants under Cd stress is well reported [6,20,21]. Cadmium, after being taken up by plant roots, is accumulated in different parts of the plants [22].…”
Section: Discussionmentioning
confidence: 90%
“…A more severe decline in plant growth under the combined stress of Cd and salinity might be due to the disturbance in photosynthetic activities, damage to the cell membrane structure, and disruption in water balance [24]. Moreover, Cd and salt stress affected many essential processes of plants such as the over-production of ROS, decrease in stomatal conductance and pigment contents, and disturbance in the uptake of essential nutrients including K [6,21].…”
Section: Discussionmentioning
confidence: 99%
“…Lead (Pb) is one of the most common HM pollutants in the environment. The Pb concentration is approximately 50 mg/kg in the soil in nature ( Bamagoos et al., 2022 ). However, due to the use of paint, Pb-containing gasoline and other Pb-containing products and the lack of effective treatment methods, the Pb concentration in the environment is much higher than the recommended safe concentration ( Salam et al., 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…In uncontaminated soils, its content in dry plant biomass and grain is in the range of 0.01–0.9 mg kg −1 [ 30 , 31 , 32 ]. It is known that Cd is a toxicant, carcinogen and teratogen [ 9 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%